1999
DOI: 10.1177/000348949910800512
|View full text |Cite
|
Sign up to set email alerts
|

Glandular Carcinoma of the Larynx: The Ucla Experience

Abstract: Glandular carcinomas of the larynx are rare tumors that constitute less than 1% of all laryngeal malignancies. A retrospective case review of 12 patients with glandular carcinomas of the larynx is presented to identify patient and tumor characteristics, therapeutic modalities, and treatment outcomes. Ten patients underwent surgical excision of the primary tumor, by either supraglottic laryngectomy, vertical partial laryngectomy, or total laryngectomy. Seven of these patients also received postoperative radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 18 publications
0
35
0
1
Order By: Relevance
“…As accessory salivary glands are exiguous in the larynx, laryngeal ACC is a rare disease, accounting for <1% of all malignant tumors in this area (10). When ACC occurs in the supraglottis, it often involves the false cords, the aryepiglottic folds and the caudal aspect of the epiglottis.…”
Section: Discussionmentioning
confidence: 99%
“…As accessory salivary glands are exiguous in the larynx, laryngeal ACC is a rare disease, accounting for <1% of all malignant tumors in this area (10). When ACC occurs in the supraglottis, it often involves the false cords, the aryepiglottic folds and the caudal aspect of the epiglottis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alavi et al presented five patients treated with surgery alone or followed by adjuvant radiotherapy with 2-year survival of 100% and a 5-year survival of 75%. Cohen et al reported eight patients with similar treatment approaches, but high early survival of 87.5% at 2 years that dropped to 44.4% at 5 years [8,26]. Recent studies, such as Calzada et al, stratified patients based on treatment modality and provided complementary data on local regional control.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal ACC is an extremely rare form of the neoplasm. The majority of instances of laryngeal ACC are located in the subglottic area, a minority of cases in the supraglottic area, and a relatively few have a glottic origin [7][8][9]. Diagnosis may be delayed because of the lack of symptoms in the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MEC tend to present with locally advanced disease due to extensive submucosal tumor spread. 10 Mucoepidermoid carcinomas are formed by 3 cell types: squamous cells, mucous cells, and intermediate cells. 10 According to the ratio of solid to cystic elements, neural invasion, necrosis, mitosis, and cellular anaplasia tumors are classified as low, medium, or high grade.…”
Section: Discussionmentioning
confidence: 99%